Flow resistance of in-line vegetation in open channel flow. Issue 3 (3rd July 2017) - Mulahasan, S.; Stoesser, T.
ABSTRACT: Open channel flow through a line of vertically oriented circular rods, designed to represent idealized bankline vegetation, is studied. Bankline vegetation is a common feature in rivers and streams and yet has not received as much attention as fully vegetated flows. Particular focus is placed on the effect of vegetation diameter on the flow resistance which is quantified via a drag coefficient. A large number of laboratory experiments of uniform flow through one-line of vegetation were carried out and drag coefficients were calculated via a momentum balance. Experimentally obtained drag coefficients are then compared to those calculated using a number of empirical expressions that have been proposed in the literature. Good agreement is generally observed. The results show that varying the diameter of the rigid emergent vegetation affects flow resistance, and that the drag coefficient of in-line vegetation exhibits limited sensitivity to the stem Reynolds number.